PARADISE: Criticality-Aware Instruction Reordering for Power Attack Resistance - Chen, Yun; Hajiabadi, Ali; Poussier, Romain; Tavva, Yaswanth; Diavastos, Andreas; Bhasin, Shivam; Carlson, Trevor E. (My University, 2025)
Power side-channel attacks exploit the correlation of power consumption with the instructions and data being processed to extract secrets from a device (e.g., cryptographic keys). Prior work primarily focused on protecting small embedded micro-controllers and in-order processors rather than high-performance, out-of-order desktop and server CPUs. In this article, we present Paradise, a general-purpose out-of-order processor with always-on protection, that implements a novel dynamic instruction scheduler to provide obfuscated execution and mitigate power analysis attacks. To achieve this, we exploit the time between operand availability of critical instructions (slack) and create high-performance random schedules.Further, we highlight the dangers of using incorrect adversarial assumptions, which can often lead to a false sense of security. Therefore, we perform an extended security analysis on AES-128 using different levels of adversaries, from basic to advanced, including a convolution neural networks-based attack. Our advanced security evaluation assumes a strong adversary with full knowledge of the countermeasure and demonstrates a significant security improvement of 556 × when combined with Boolean Masking over a baseline only protected by masking and 62,500× over an unprotected baseline. The resulting overhead in performance, power, and area of Paradise is 3.2%, 1.2%, and 0.8% respectively.1